(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The distinctive multiparty Indian polity has transformed from ‘One Party Dominance’ system to a new mode of representation in the form of alliance politics. The experiments with the alliance politics started even before the independence period and after passing through the various crucial junctions of the Indian political history it established in the form of present mature and stable alliance governments. The new paradigm shift has been completely institutionalized since 2004 general elections. The BJP adopted electoral strategy of alliances early than the Congress and formed governments under the name of a grand alliance the NDA and the Congress officially adopted that policy before the 14th general elections in 2004. The alliance politics was the only panacea for the Congress to regain its lost credibility and eroded support base. Although there were other political formations in the contest yet the main contest was between the BJP-led NDA and the Congress-led alliance that was unnamed before the elections. The main objective of this paper is to review alliance strategies of the BJP and the Congress, elections issues and outcomes of alliances. The words ‘coalition’ and ‘alliance’ are being used interchangeably in different studies and in this paper the word alliance is being used.